Earthly Measures - Hirsch, Edward (Alfred A. Knopf)
Edward Hirsch (Chicago, 1950) poeta norteamericano es autor de For the Sleepwalkers; Wild Gratitude; The Night Parade; Earthly Measures. Obtuvo el National Book Critics Circle Awards en 1986.